Hedges in Arabic Language that Occured in Daily Conversation in Family Domain - Nasir, Amin (Journal of English Teaching and Learning Issues, 2018)
The phenomena of hedges are commonly found and used by the people in their daily communication. Hedges expressions are kind of expressions which are showing a doubtness or an uncertainty of the speaker towards a proposition they uttered. Hedging can be defined as a mitigating device that is used to reduce the impact of an utterannce. It is kind of rhetorical strategy. People may have their own reason why they use hedges in their utterance. Hedges have some functions such as to reduce threat face, to serve politeness strategy and to being more price. This research use a qualitative research which only focus in analysing the use of hedges that occured in daily conversation in arabian family domain. The result of this research indicate that there are some hedges device expression in arabic language such as ‘taqribaan’ which means ‘around’, ‘aro’ that means ‘I think’, and ‘qobaltu’ which means ‘I guess’.